Left atrial size and risk of stroke in patients in sinus rhythm - Overvad, Thure Filskov; Nielsen, Peter Brønnum; Larsen, Torben Bjerregaard; Søgaard, Peter (Thrombosis and Haemostasis, 2016)
Little is known about the risk of stroke associated with left atrial enlargement in patients in sinus rhythm, and whether such patients may have an unmet need for thromboprophylaxis. In this systematic review we summarise the existing evidence concerning left atrial size and risk of stroke in patients in sinus rhythm. Nine cohort studies were identified, analysing a total of 67,875 participants and 3,093 stroke outcomes. Rates of stroke per 100 person-years in patients with left atrial enlargement and in sinus rhythm ranged from 0.59 in a population-based cohort to 2.06 in patients referred for echocardiography. All studies reported a higher risk of stroke with larger/enlarged left atrium compared to smaller/normal sized left atrium. Two studies found indications of modification by sex, with only positive associations observed in women. Left atrial enlargement may represent an important predictor of stroke across a variety of patient populations in sinus rhythm. The underlying aetiology explaining this observed higher risk is likely to be multifactorial and not confined to a potential direct effect of left atrial enlargement on thromboembolic risk. Formal stroke risk stratification among patients with left atrial enlargement may further help identify patients who stand to gain from preventive antithrombotic therapy.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Left atrial size; left atrial enlargement; sinus rhythm; stroke/prevention; thromboembolism